2015
DOI: 10.1186/s40462-015-0032-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and visualisation of movement: an interdisciplinary review

Abstract: The processes that cause and influence movement are one of the main points of enquiry in movement ecology. However, ecology is not the only discipline interested in movement: a number of information sciences are specialising in analysis and visualisation of movement data. The recent explosion in availability and complexity of movement data has resulted in a call in ecology for new appropriate methods that would be able to take full advantage of the increasingly complex and growing data volume. One way in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
140
0
4

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(144 citation statements)
references
References 204 publications
(273 reference statements)
0
140
0
4
Order By: Relevance
“…The integration of different research fields might allow to apply principles revealed in animal superorganisms to team sports performance analysis and vice versa [67]. The analysis of movement patterns of individuals therefore will benefit from a close collaboration by researchers of different fields in which new movement analysis and visualization methodologies can arise [68] and help to understand collective behavior in the wild or/and under restricted conditions like team sports or lab experiments.…”
Section: Group Behavior and Movementmentioning
confidence: 99%
“…The integration of different research fields might allow to apply principles revealed in animal superorganisms to team sports performance analysis and vice versa [67]. The analysis of movement patterns of individuals therefore will benefit from a close collaboration by researchers of different fields in which new movement analysis and visualization methodologies can arise [68] and help to understand collective behavior in the wild or/and under restricted conditions like team sports or lab experiments.…”
Section: Group Behavior and Movementmentioning
confidence: 99%
“…Context-awareness has recently received attention in many movement research directions in the areas of geographic information science (GIScience), [12][13][14][15] geocomputation (i.e., a wide array of spatial analytical methods and tools 16 ), visual analytics 17,18 (i.e., analytical reasoning facilitated by interactive visual interfaces 19 ), remote sensing 20 and tracking, 21 spatial data mining and knowledge discovery, or a combination thereof. The majority of this research has thus far merely used context as ancillary information to better understand mobilities, such as event-based movement analysis, 22 similarity measurement of trajectories, 23,24 uncertainty reduction and ranking in road networks, 25 uncertainty modeling associated with moving objects, 26 modeling spatial relevancy in context-aware systems, 27 determining significant places from mobility data, 28 visual analysis of movement behavior, 29 simulation models for movement, 30 analysis of human mobility patterns 31 and predictions, 32 and location prediction, 33 among others.…”
Section: Introductionmentioning
confidence: 99%
“…Trajectory visualization plays an important role in the analysis of movement [26]. It allows us to understand movement patterns of various kinds of moving "objects" in a geospatial context.…”
Section: Trajectory Visualizationmentioning
confidence: 99%
“…These tend to be stored as nested lists, but can also be visualized as directed acyclic graphs. A recent example of a sophisticated infrastructure for the storage (banking), visualization, and interactive working with complex linguistic analyses is the INESS Infrastructure for the Exploration of Syntax and Semantics [75,99], 26 which is part of CLARIN, 27 the Common Language Resources and Technology Infrastructure, which in turn provides support and resources for research in the humanities and social sciences that is concerned with digital language data. INESS augments existing tree and AVM representations with further visualization possibilities that link and align information across complex structures and support disambiguation.…”
Section: Text Visualizationmentioning
confidence: 99%